Analisa Stabilitas Bendung (Studi Kasus: Bendungan Pacal Kabupaten Bojonegoro) - Muhammad Yusuf Firmansyah; Farah Putri Purwahono (Jurnal Sains dan Teknologi, 2023)
Pacal Dam as one of the infrastructures that has an important role in the life of the people of Bojonegoro Regency. Pacal Dam is one of the providers of water resources in meeting the needs of the surrounding community in irrigation and agriculture aspects. In addition, the Pacal Dam is also a water conservation medium which is one of the efforts to reduce surface runoff originating from the upstream of the river so that flooding does not occur downstream. Therefore, in planning, it is necessary to accurately calculate the stability of the weir. Spiral stability calculations are carried out to determine whether the weir is stable enough to withstand the external forces that occur. Factors that can affect stability include the weight of the weir, active and passive earth pressure forces, and the resulting uplift. In the stability analysis of the Pancal Dam, it was found that under normal conditions the SF (safety factor) result was 1.6082822, while in flood conditions the SF result was 1.55237, where the SF value was > 1.5 so it can be concluded that the weir planning has been able to withstand the overturning moment caused by water pressure, soil, and uplift pressure in flood conditions.